Management of pericatheter dialysate leaks using hemostatic agents. Issue 4 (17th February 2022) - Eray, İsmail Cem; Topal, Ugur; Balal, Mustafa; Paydas, Saime
Abstract: Continuous ambulatory peritoneal dialysis (CAPD) is one of the treatment modalities used in end‐stage renal disease. The most common cause of failure is catheter‐related complications. Dialysate leak represents a major noninfectious complication of PD. Here, we aimed to present the results of patients who had pericatheter dialysate leak following PD catheterization and who were administered a hemostatic agent (HaemoCer Plus, BioCer, Germany) around the catheter and the tunneled segment under the subcutaneous tissue under local anesthesia. We performed a local procedure on six patients in total. No major complications developed in any of the patients at postoperative follow‐up. Five patients started to receive PD uneventfully within postoperative 3 days with no dialysate leak. We believe that this practice is effective in the management of peritoneal dialysate leak. The hemostatic agents administered in the present study can manage dialysate leak and ensure safe use of the catheter.